Nutrition in Lifestyle Medicine - Rippe, James M. (Springer International Publishing : Imprint: Humana Press, 2017)
This newest addition to the Nutrition and Health series focuses on nutrition's key role in lifestyle interventions to prevent and manage diseases. The book pays particular attention to nutritional considerations related to obesity, diabetes, and cardiovascular disease. Edited by cardiologist, Dr. James Rippe, a well-known expert in the nascent specialty of Lifestyle Medicine, Nutrition in Lifestyle Medicine will also focus on a variety of specialized areas such as nutrition for athletes and physically active individuals, hydration, and nutrition throughout the life cycle (spanning from children to individuals over the age of 60). In addition, chapters will be included on controversies in nutrition, such as health effects of added sugars and saturated fatty acids in the diet. Finally, specialized chapters will be included in such areas as nutrition for women, nutrition for men, nutrition for latinos, the use of supplements, communication about nutrition, public policy issues, and the interface between nutrition and physical activity. Lifestyle Medicine, supported by the American Journal of Lifestyle Medicine, Dr. Rippe's textbook Lifestyle Medicine (CRC Press, 2013) and American College of Lifestyle Medicine (ACLM), is a new national medicine specialty that stresses the use of lifestyle interventions in the treatment and management of disease. Its practitioners effectively manage medical treatments alongside the lifestyle interventions, for example lowering insulin treatment for patients with diabetes, reducing the dose of anti-hypertension medications for people with hypertension, and prescribing certain medical interventions that aid in smoking cessation.
Keywords: Medicine.; Health promotion.; Clinical nutrition.; elektronické knihy; electronic books